2022
DOI: 10.1021/acs.jpcc.2c04731
|View full text |Cite
|
Sign up to set email alerts
|

NO Degradation on the Anatase TiO2 (001) Surface in the Presence of Water

Abstract: Nitric oxide (NO) is known to degrade to nitric acid (HNO3) on anatase TiO2 facets under visible light irradiation in the presence of water. However, the exact role that water plays in this photoreaction is not fully understood. By employing the density functional theory (DFT) and time-dependent density functional tight binding (TD-DFTB), we show the viability of two suggested degradation pathways involving water. Both reaction pathways are triggered by a charge transfer excitation from the NO molecule to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…407.5 eV), and the peaks are called the triplet and singlet peaks, respectively [9]. The N 1s spectrum recorded during exposure does not give rise to peaks consistent with NO adsorption, which would appear at a BE of ~401 eV [29]. However, a broad peak can be fitted to the spectrum beneath the gas phase peak with a centre of gravity at 407.5 eV, a BE consistent with the formation of NO 3 − [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…407.5 eV), and the peaks are called the triplet and singlet peaks, respectively [9]. The N 1s spectrum recorded during exposure does not give rise to peaks consistent with NO adsorption, which would appear at a BE of ~401 eV [29]. However, a broad peak can be fitted to the spectrum beneath the gas phase peak with a centre of gravity at 407.5 eV, a BE consistent with the formation of NO 3 − [5].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the conversion of NO to NO 3 − results in the formation of HNO 3 and NO 3 − species at the surface through reaction with water or surface OH [5], catalysed by UV light. Although no UV light was deliberately introduced into the system here, the cell was illuminated with an LED lamp to allow sample positioning, and absorption of X-rays will also result in the formation of the holes in the valence band which are required for the reaction to progress [5,29]. In order to investigate this further, the effect of exposing the powder to 1 mbar NO + 1 mbar H 2 O, simultaneously, was investigated.…”
Section: Reaction With So 2 Gasmentioning
confidence: 99%
“…In contrast, both samples showed slight photocatalytic activity under blue-LED irradiation, and the A-TiO 2 -450 sample showed the highest activity. This fact could be caused by the photoexcitation of the NO-TiO 2 complex or photopromotion of electrons from the color centers, both photoinduced processes injecting electrons to the TiO 2 CB and which should lead to NO-species degradation and producing HNO 3 , HONO, or NO 2 , as recently reported by Gupta et al To study the photodecomposition of the NO-TiO 2 surface complex, we measured the final pH of the solutions after the photocatalytic experiments (under blue-LED irradiation) using A-TiO 2 -450 samples, and we did not find any changes. These photoinduced electrons in the CB of TiO 2 can be further transferred to the molecular oxygen, leading to the formation of • OH radicals (in low amounts undetectable by ESR-spin trapping) via a reductive path (H 2 O 2 reduction) (Scheme ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ammonia, this molecule at temperatures beyond 300 °C in oxygenated atmospheres undergoes thermal decomposition to NO or NO 2 , and both products can generate strong interactions with TiO 2 , leading to the generation of surface NO-TiO 2 complexes and oxygen vacancies, which could be responsible for visible light absorption. Moreover, ammonia at temperatures higher than 550 °C decomposes toward N 2 and H 2 , and some studies have mentioned that H 2 can induce the formation of V o through a mechanism similar to the production of black TiO 2 …”
Section: Introductionmentioning
confidence: 99%
“…The photo‐oxidation of NO x on TiO 2 to produce nitrate has proved to be effective. Gupta et al 130 investigated the photo‐oxidative degradation of NO on anatase TiO 2 (001) surface in the presence of explicit water with DFT and TD‐DFTB calculations. They proposed two paths for the initial charge transfer excitation step: the direct reaction with water forms HONO, or NO 2 is formed with the assistance of lattice O.…”
Section: Electron Hole and Photocatalysismentioning
confidence: 99%